(E)-2-(4-Chlorophenoxy)-N′-(pyridin-4-ylmethylidene)acetohydrazide - Rao, Xiao-jin (International Union of Crystallography, 2012)
In the title compound, C14H12ClN3O2, the acylhydrazone base [C(=O)—N—N=C] is essentially planar, with an r.m.s. deviation of 0.0095 Å, and makes a dihedral angle of 12.52 (10)°with the pyridine ring. In the crystal, molecules are linked via pairs of N—H⋯O hydrogen bonds, forming inversion dimers with an R 2 2(8) graph-set motif. The dimers are linked via C—H⋯π interactions forming chains along [101].